Africa is in a mess what went wrong and what should be done - Mwakikagile, Godfrey (Dar es Salaam New Africa Press, 2006)
This is a revised and updated edition in which the author examines the problems of post-colonial Africa. He contends that the problems have existed since independence in the sixties and have been made worse through the years by a combination of factors. It is a blunt assessment and prescribes some solutions to Africa's problems focusing on internal factors but without exonerating external forces from what has happened on the continent through the decades.
Includes bibliographical references.
Keywords: Political corruption--Africa.